Triple-Rule-Out Computed Tomography Scanning for the Diagnosis of a Mediastinal Tumor - Useini, Dritan; Taghiyev, Zulfugar; Bechtel, Matthias; Strauch, Justus (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Thymomas are rare tumors that commonly lie in the anterior mediastinum. The arteries supplying thymomas branch from the internal thoracic arteries and their collaterals. This report presents a patient with huge mediastinal thymoma, whose sensational vascularization is ensured directly by a single dominant tributary branch of the left internal thoracic artery. After initially performed computed tomography angiography, the tumor was suspect to be vascularized from the right coronary artery. Triple-rule-out computed tomography scan was a key step for accurate radiologic diagnosis.
Keywords: thymus; computed tomography; TRO-CT scan